Analisis Sentimen Mengenai Vaksin Sinovac di Media Sosial Twitter Menggunakan Metode NaÃ¯ve bayes Classification - Aldisa, Rima Tamara; Azizah, Azizah; Abdullah, Mohammad Aldinugroho (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
The Sinovac vaccine is an example of a type of inactivated vaccine. The government bought Sinovac, Novavax, AstraZeneca, and Pfizer vaccines. This vaccine is used to treat the Covid-19 pandemic. This vaccine is used to treat the Covid-19 pandemic. The role of the Indonesian people in expressing and stating the pros and cons often involves public services that are easily accessible by many people, namely social media, one of which is Twitter. This can be used as material to analyze who produces data in support of decisions. The technique that can be used is sentiment analysis. The method used in this study is the NaÃ¯ve bayes Classification. The purpose of this study was to determine the value of sentiment analysis on the Sinovac vaccine using the Naive Bayes Classification method on Twitter social media using Indonesian. The result of this research is the final probability value based on the condition 0.000002765 for positive and 0.000000359 for negative. A response with a positive comment has a greater probability of a response with a negative comment.